2004
DOI: 10.1097/01.ju.0000110297.98725.25
|View full text |Cite
|
Sign up to set email alerts
|

Modified Corporoplasty for Ventral Penile Curvature: Description of the Technique and Initial Results

Abstract: The modified Nesbit procedure that we propose allows complete and definitive correction of ventral penile curvature without any manipulation of the dorsal bundle. Excellent penile straightening and the lack of significant postoperative complications result in high patient satisfaction rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 17 publications
2
22
0
1
Order By: Relevance
“…Surgical correction was found to result in a signifi cant improvement in the patient ' s overall relationship, as well as his sexual relationship, confi dence, libido and general satisfaction [ 22 ] . The highest rates of complete penile straightening, preservation of erectile function and overall satisfaction with our technique are in accordance with results of other published series [ 16,19,23,24 ] .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Surgical correction was found to result in a signifi cant improvement in the patient ' s overall relationship, as well as his sexual relationship, confi dence, libido and general satisfaction [ 22 ] . The highest rates of complete penile straightening, preservation of erectile function and overall satisfaction with our technique are in accordance with results of other published series [ 16,19,23,24 ] .…”
Section: Discussionsupporting
confidence: 81%
“…More recently Giammusso et al . [ 19 ] and Rolle et al . [ 20 ] introduced interesting modifi cations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study based on this technique done in 12 patients with penile curvature reported that penile straightening was achieved in all patients, while 67% of Review them reported penile shortening (1-2.5 cm), although the decreased length did not cause interference with sexual activity. No surgery-related complication, such as pain or loss of sensitivity, was reported, and 83% of the patients reported full satisfaction [48] .…”
Section: Surgical Treatmentmentioning
confidence: 98%
“…Following repair in another report, all patients showed elimination of penile curvature with preserved erectile function in 92% and an 83% full satisfaction rate. 13 Therefore, surgical management provides excellent rates of penile straightening and patient satisfaction.…”
Section: Congenital Penile Curvaturementioning
confidence: 99%